The response of the central auditory nervous system to sound in normal hearing adults with and without HIV/AIDS : an fMRI study - Soer, Maggi E. (Magdalena Elizabeth) (University of Pretoria, 2018)
Thesis (PhD)--University of Pretoria, 2017.